1014Maternal educational qualification and child's birth weight: Findings from Office for National Statistics Longitudinal Study. (2nd September 2021) - Pikhartova, Jitka; Stuchbury, Rachel; Shelton, Nicola
Abstract: Background: Lower maternal education was found to be associated with lower child's birthweight which in turn was a possible risk factor for later poor health. Presented research aims to assess the association between maternal education and singleton's birthweight in large UK data, accounting for characteristics such child's gender, parity, maternal age, partnership status, ethnicity, and household socioeconomic characteristics. Methods: Using England and Wales Office for National Statistics Longitudinal Study (ONS-LS), data from over 240, 000 children born since 1981 to ONS-LS sample mothers were used. Maternal education was derived into 3 categories (below secondary, complete secondary education, degree and higher). Results: Crude analysis confirmed significant association between the level of education and birthweight in each Census cohort (p < 0.001). In adjusted models, the education gradient was partly explained but remained strongly significant, and substantially increased over the years: for example, the birthweight difference between those with below secondary educated mothers and those with degree increased from 29 to 92 grams (p for change<0.001). Conclusions: Our findings support previous evidence using different, usually smaller, population samples. Children of mothers with no or low qualification are more prone to be born with lower birthweight leading potentially into health disadvantages in their later life. Our results suggest that the inequalities in birth weight increased over the last 35 years. Key messages: Low levels of maternal education predicts low birthweight in children.